2018
DOI: 10.1177/0309364617729925
|View full text |Cite
|
Sign up to set email alerts
|

A model to facilitate implementation of the International Classification of Functioning, Disability and Health into prosthetics and orthotics

Abstract: Background:The International Classification of Functioning, Disability and Health is a classification of human functioning and disability and is based on a biopsychosocial model of health. As such, International Classification of Functioning, Disability and Health seems suitable as a basis for constructing models defining the clinical P&O process. The aim was to use International Classification of Functioning, Disability and Health to facilitate development of such a model.Proposed model:A model, the Prostheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…This is not surprising. The ICF has been promoted for use in O&P to encourage a holistic and patient-centered approach 109 and has been proposed as a framework to guide clinical reasoning. 110 While individuals' use of prostheses and orthoses is classified within the environmental factors category of the ICF, the ICF does not provide the level of detail nor the quality characteristics necessary for clinical interpretation and reasoning.…”
Section: Implications For Oandp Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising. The ICF has been promoted for use in O&P to encourage a holistic and patient-centered approach 109 and has been proposed as a framework to guide clinical reasoning. 110 While individuals' use of prostheses and orthoses is classified within the environmental factors category of the ICF, the ICF does not provide the level of detail nor the quality characteristics necessary for clinical interpretation and reasoning.…”
Section: Implications For Oandp Educationmentioning
confidence: 99%
“…This is not surprising. The ICF has been promoted for use in O&P to encourage a holistic and patient-centered approach 109 and has been proposed as a framework to guide clinical reasoning. 110…”
Section: Implications For Oandp Educationmentioning
confidence: 99%
“…16 In accordance with the International Classification of Functioning Disability and Health (ICF) model, health professionals have a responsibility to direct treatment toward enabling their clients to perform desired activities and to facilitate participation of their clients in all areas of life. 14,17 As providers of assistive technologies, prosthetists/orthotists can play an important role in helping their clients to meet goals related to participation in sexual activities, as a means of maintaining or establishing sexual relationships. Individuals who have undergone an amputation have indicated that the development of prostheses and assistive devices to facilitate sexual activity would improve their sexual life.…”
Section: Boxmentioning
confidence: 99%
“…49 To develop students' clinical reasoning skills in a systematic way, students could use frameworks to map and compare variables that affect desired technical and functional outcomes. 50,51 Once students identify a pathway to make clinical decisions about a case, they can explore how various contexts might alter the outcomes and, thus, the clinical decision. Finally, to further develop critical inquiry, educators could use prosthetic threshold concepts (i.e.…”
Section: Nurture a Culture Of Critical Inquiry And Promote Evidence-bmentioning
confidence: 99%